PENGGUNAAN TEKNIK NUMBERED HEADS TOGETHER DALAM PENINGKATAN PEMBELAJARAN IPA PADA SISWA KELAS V SEKOLAH DASAR - Handayani, Lilis Saputri (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Use of Numbered Heads Together Technique in Science Learning Improvement to The Fifth Graders of Elementary School. This research purposes to improve science learning to the fifth graders of elementary school by using Numbered Heads Together technique. This research was conducted in two cycles consisting of planning, acting, observing, and reflecting. The research subjects were students and teacher. The source data were the teacher, students, and observers. Data collection techniques using test, observation, and interviews. Validity data using triangulation techniques and sources. Analysis of the data used descriptive qualitative analysis and descriptive statistics. The results of this research showed that the use of Numbered Heads Together technique can improve science learning to the fifth graders of elementary school.   Keyword: Technique, Numbered Heads Together, Science Learning   Abstrak: Penggunaan Teknik Numbered Heads Together dalam Peningkatan Pembelajaran IPA pada Siswa Kelas V Sekolah Dasar. Penelitian ini bertujuan untuk meningkatkan pembelajaran IPA pada siswa kelas V sekolah dasar dengan teknik Numbered Heads Together. Penelitian dilaksanakan dalam dua siklus, terdiri atas perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah siswa dan guru. Data penelitian berasal dari guru, siswa, dan observer. Teknik pengumpulan data menggunakan tes, observasi, dan wawancara. Validitas data menggunakan triangulasi teknik dan sumber. Analisis data menggunakan deskriptif kualitatif dan deskriptif statistik. Hasil penelitian menunjukkan penggunaan teknik Numbered Heads Together dapat meningkatkan pembelajaran IPA pada siswa kelas V sekolah dasar.   Kata Kunci: Teknik, Numbered Heads Together, Pembelajaran IPA